2020
DOI: 10.1097/md.0000000000021733
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in dermatomyositis

Abstract: Dermatomyositis (DM) is an idiopathic inflammatory myopathy that is closely related to malignant diseases. Our study aims to investigate the incidence and predictive factors for occurrence of malignancy among DM patients from Central China. We performed a retrospective, paired, case–control study of 736 DM patients admitted to the First Affiliated Hospital of Zhengzhou University between 2010 and 2017. We paired the 65 patients with malignancy with age-matched and sex-matched patients without malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…The first reported case of DM as a paraneoplastic phenomen was recognised by Stertz, who reported inflammatory myopathy in a patient with gastric adenocarcinoma 5. Paraneoplastic DM is now better recognised, although evidence to quantify just how many DM cases are associated with malignancy is variable; anything between 6% and 60% 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reported case of DM as a paraneoplastic phenomen was recognised by Stertz, who reported inflammatory myopathy in a patient with gastric adenocarcinoma 5. Paraneoplastic DM is now better recognised, although evidence to quantify just how many DM cases are associated with malignancy is variable; anything between 6% and 60% 6…”
Section: Discussionmentioning
confidence: 99%
“…A study of 65 patients with paraneoplastic DM in China, 2020, found only 32% of cancers were diagnosed before the occurrence of DM: 14% were within the most recent 1 year, 17% were within 3 years and 23% within 5 years 6. Another study, published 2001, found only 83 of 198 cases were diagnosed with cancer prior to their diagnosis of DM 2.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, IP was detected subsequent to a breast cancer diagnosis, with further evaluation revealing positive anti-EJ antibodies. Although malignancies are common among patients with dermatomyositis [ 2 ], reduced incidence of malignancies has been observed in patients with both IP and dermatomyositis [ 3 ]. Despite documented cases of patients with coexisting ASSD, IP, and breast cancer [ 4 , 5 ], standardized treatment guidelines for those with IP in conjunction with malignancy have yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…1 DM has been linked with various cancers, including lymphoma, lung, ovary, colorectal, pancreatic, stomach, and breast cancer. 1,4 Urothelial cancer is less common, though it has been reported as the fifth most common cancer type among CAD patients with anti-TIF1-γ positivity. 3 In some such cases, DM manifestation acted as a clinical indicator of TCC recurrence, manifesting prior to cancerrelated symptoms and prompting timely investigation to rule out cancer recurrence.…”
mentioning
confidence: 99%
“…Despite this, immunosuppressive therapy is often necessary to control DM symptoms, especially when its manifestation includes dysphagia or causes severe functional limitation. Immunosuppression in CAD poses potential risks, however, in that it may: (1) facilitate malignancy propagation, 1 (2) increase risk of complications from concurrent cancer treatment, or (3) decrease efficacy of cancer therapy. These risks are exemplified by the case presented here, though in each case the benefits of steroids were felt to outweigh the risks after review of the literature.…”
mentioning
confidence: 99%